IMPACT OF CUSTOMER RELATIONSHIP MANAGEMENT ON CUSTOMER LOYALTY IN THE INSURANCE SECTOR - Sanyasi, Bishnu Maya; Dhakal, Keshar Nath; Rajnish Ratna (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Customer Relationship Management (CRM) is now an important dimension for every corporation. It has been seen that in oligopolistic marketing, the relationship with the customers is essential for the financial institution and insurance companies. Since perceptions and expectations of customers are continually evolving and it is being difficult for service sectors to manage and provide effective services. Therefore, for the proper management of services and meeting the expectations of customers, companies have a dedicated department called Customer Relationship Management (CRM). With the advancement of technology, every company is taking major possible steps to insure customer loyalty for the benefits of companies in the long run. The purpose of this study is aimed at finding the impact of Customer Relationship Management (CRM) on customer loyalty in the insurance sector of Bhutan. Both qualitative and quantitative research design is being used for the collection of the data from identified respondent. Data is collected from 258 customers using a well-designed questionnaire. Data analysis is done with SPSS 21. The results of data analysis revealed a significant, positive, and strong impact of CRM practices on customer loyalty. It is likewise reported that the dimensions of CRM such as responsiveness, service orientation, reliability and personal attention are having significant impact on customer loyalty while no significant impact is reported for convenience, product varieties and promotional activities of the company. Additionally, the dimensions like SO (Service orientation) and customer reliability have the highest impact factor among other dimensions of CRM. It is thus concluded that satisfaction of customers with CRM practices will tend to maintain long-term relationships with the company and eventually expand the profitability of the insurance sector.